Use of botulinum toxin type A in rheumatic diseases - O. N. Egorova; B. S. Belov; E. G. Sazhina (Современная ревматология, 2021)
The article presents an analysis of modern data on the antinociceptive effectiveness of botulinum toxin type A (BTA) in rheumatic diseases (RD). The prospects for the use of BTA in the treatment of pain in different RDs are discussed. We searched for publications in the Medline, Pubmed, Cochrane Library databases. Analysis of literature data has shown that BTA can become an additional method of pain management in many RDs.